An Analysis of Moral Value in Guru-Guru Gokil Movie Based on Its Main Characters - Nur Mardiyani Fauziah Fuad; Raisa Anakotta; Rizqi Claudia Wardani (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2024)
The objective of this research is to analyse the moral values of the characters Taat Pribadi, Rahayu, Nirmala, Nelson Manulang, Purnama, dan Indah. Related to the research objective, a descriptive qualitative research design was used. This research design used library research. The main characters studied in this movie are 6 teachers. The writer chose guru-guru gokil movie which focused on the teacher because currently, the moral value of the teacher is quite low so that through this movie the teacher can learn good moral values and implement it in their lives. In collecting data, the write download guru-guru gokil movie from the internet and watch the movie and then observed it. In analyzing the data, the writer uses the theoretical basis of moral value according to several experts and thesis to find out what the moral values are in the movie and classify it. The research findings show that there are 13 good moral values that are honesty, bravery, confidence, self-discipline, purity, hard work, loyalty and trustworthy, respect, affection, caring, fair, responsibility, and cooperativeness. That moral value should be applied in the daily life of teacher candidates and the teachers in school. It can be concluded that guru-guru gokil movie is worthy of being watched by teachers to increase moral values in their lives. The research implications of this study suggest that the findings can serve as a valuable resource for teacher training programs and educational institutions. By identifying and classifying the moral values depicted in the